Toxicity Test Of N-Hexan Fraction, Ethyl Acetate, And Chloroform Red Gedi Plant (Abelmoschus Manihot L. Medik) With Brine Shrimp Lethality Test (BSLT) Method: Toxicity Test Of N-Hexan Fraction, Ethyl Acetate, And Chloroform Red Gedi Plant (Abelmoschus Manihot L. Medik) With Brine Shrimp Lethality Test (BSLT) Method - atyrah andi; Nurlina Ibrahim (Media Publikasi Penelitian Kebidanan, 2023)
Red gedi (Abelmoschus manihot L. Medik) is a tropical plant in the family Malvaceae that is used empirically by the community of Palu City as an anti-cancer. Red gedi leaves contain flavones that have high antioxidant activity. This study aims to determine the toxicity potential by means of the LC50 value of red gedi leaf extract within n-hexane fraction, ethyl acetate fraction, and chloroform fraction using the Brine Shrimp Lethality Test (BSLT) method. The BSLT method used Artemia salina Leach larvae tested with all fractions at the concentration of 25ppm, 500ppm, 100ppm, 200ppm, and 500ppm. The extraction process began with the maceration method of red gedi leaf simplicia with ethanol 96% solvent. The extract obtained from the maceration process was concentrated with a rotary evaporator, then 30 ml of water was added to the extract for further partitioning purposes. The solution from the previous stage was first partitioned using n-hexane solvent to obtain the n-hexane fraction, then the insoluble extract in n-hexane was partitioned with ethyl acetate so as to obtain ethyl acetate fraction, then finally the extract which was insoluble in ethyl acetate was further partitioned with chloroform, so the chloroform fraction is obtained. The final toxicity test, performed using the BSLT method, yielded LC50 values ​​of 81.563 ppm, 333.199 ppm, and 104.591 ppm for n-hexane, ethyl acetate, and chloroform fractions respectively. It can be concluded that the n-hexane fraction of red gedi leaves exhibits a stronger toxic effect compared to the chloroform and ethyl acetate fractions of red gedi leaves.